Scenario Planning for Bahagia Primary Clinic to Navigate Future Uncertainties in the Healthcare Industry - Susanto, James Daniel; Hermawan, Pri (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
In the healthcare industry, first-level primary care clinics face challenges from the future uncertainties that affect the clinic’s operational ability. Bahagia Primary Clinic, a long-standing family-owned business operating for over 40 years, wants to be passed down to the next generation, but at present, the clinic does not have a long-term plan, which creates contradictions and gaps in its vision of becoming a sustainable family business. This study uses the scenario planning framework to help the clinic prepare for the next 5 years by identifying the key focal issues, driving forces, external and internal environments, early warning signals, and business solutions. By using interviews, content analysis, PESTEL analysis, Porter’s Five Forces analysis, and SWOT analysis, the 12 key driving forces were identified. Government Policy & Regulation and Internal HR & Management emerged as the most critical, impactful, and uncertain driving forces, thus forming the basis for the 2×2 scenario planning matrix. Four scenarios were created, they are the Steady Crew in Stormy Seas, Titanic, Calm Tailwinds, and Missed Tailwinds, each with implications, options, and business solutions. The results provide business solutions that emphasize on digitalization, human capability, and better service quality to strengthen the clinic’s resilience.